Indirect interaction of 13C nuclear spins in diamond with NV centers: simulation of the full J-coupling tensors - Nizovtsev, Alexander; Pushkarchuk, Aliaksandr; Kuten, Semen; Michels, Dominik; Lyakhov, Dmitry; Kargin, Nikolai; Kilin, Sergei (Frontiers in Quantum Science and Technology, 2024)
Recent experiments on the detection, imaging, characterization and control of multiple 13C nuclear spins, as well as of individual 13C–13C dimers in diamond using a single nitrogen-vacancy (NV) center as a sensor, along with the impressive progress in increasing the spectral resolution of such sensor (up to sub-Hertz), have created a request for detailed knowledge of all possible spin interactions in the studied systems. Here, we focus on the indirect interaction (J-coupling) of 13C nuclear spins in diamond, which was not previously taken into account in studies of NV centers. Using two different levels of the density functional theory (DFT), we simulated the full tensors nJKL (K, L = X, Y,Z), describing n-bond J-coupling of nuclear spins 13C in H-terminated diamond-like clusters C10H16 (adamantane) and C35H36, as well as in the cluster C33[NV−]H36 hosting the negatively charged NV− center. We found that, in addition to the usually considered isotropic scalar nJ-coupling constant, the anisotropic contributions to the nJ-coupling tensor are essential. We also showed that the presence of the NV center affects the J-coupling characteristics, especially in the case of 13C–13C pairs located near the vacancy of the NV center.